Detection of Audio-Visual Integration Sites in Humans by Application of Electrophysiological Criteria to the BOLD Effect - Calvert, Gemma A.; Hansen, Peter C.; Iversen, Susan D.; Brammer, Michael J. (NeuroImage (Orlando, Fla.), 2001)
Electrophysiological studies in nonhuman primates and other mammals have shown that sensory cues from different modalities that appear at the same time and in the same location can increase the firing rate of multisensory cells in the superior colliculus to a level exceeding that predicted by summing the responses to the unimodal inputs. In contrast, spatially disparate multisensory cues can induce a profound response depression. We have previously demonstrated using functional magnetic resonance imaging (fMRI) that similar indices of crossmodal facilitation and inhibition are detectable in human cortex when subjects listen to speech while viewing visually congruent and incongruent lip and mouth movements. Here, we have used fMRI to investigate whether similar BOLD signal changes are observable during the crossmodal integration of nonspeech auditory and visual stimuli, matched or mismatched solely on the basis of their temporal synchrony, and if so, whether these crossmodal effects occur in similar brain areas as those identified during the integration of audio-visual speech. Subjects were exposed to synchronous and asynchronous auditory (white noise bursts) and visual (B/W alternating checkerboard) stimuli and to each modality in isolation. Synchronous and asynchronous bimodal inputs produced superadditive BOLD response enhancement and response depression across a large network of polysensory areas. The most highly significant of these crossmodal gains and decrements were observed in the superior colliculi. Other regions exhibiting these crossmodal interactions included cortex within the superior temporal sulcus, intraparietal sulcus, insula, and several foci in the frontal lobe, including within the superior and ventromedial frontal gyri. These data demonstrate the efficacy of using an analytic approach informed by electrophysiology to identify multisensory integration sites in humans and suggest that the particular network of brain areas implicated in these crossmodal integrative processes are dependent on the nature of the correspondence between the different sensory inputs (e.g. space, time, and/or form).